Analisis Kemampuan Pemecahan Masalah Mahasiswa Program Studi Pendidikan Matematika UNIKA Weetebula dalam Menyelesaikan Soal Tes Potensi Akademik - Making, Samuel Rex Mulyadi; Kaleka, Yohanis Umbu; Lede, Yulius Keremata (Indo-MathEdu Intellectuals Journal, 2024)
The Academic Potential Test is a test that aims to measure a person's abilities in the general academic field. This test is also often associated with intelligence. Currently, apart from selecting prospective students at universities, The Academic Potential Test has also become a standard test in the selection of Civil Servant Candidates and in the recruitment of private employees and employees of State-Owned Enterprises. Based on the background above, it is necessary to measure the ability of students from the Mathematics Education Study Program at Catholic University Weetebula in solving test questions. This needs to be done as a first step in determining the abilities of prospective graduates. The method used in this research was by giving a written test in the form of test questions to 56 students and interviews with 9 students who took the test. The instruments used were 40 test questions and an interview guide. The data analysis techniques used are reduction, presentation and drawing conclusions. The test results show that students who get the low category are 84%, students who get the Average category are 7% and students who get the high category are 9%. The interview results showed that students were able to understand the test questions given, but students had difficulty determining how to solve them, so students were unable to determine the correct answer